PENGARUH ATRIBUT PRODUK BALI STUTI TERHADAP KEPUASAN KONSUMEN DI KOTA DENPASAR BALI - Oviani, Gusti Ayu; Listiani, Putu Ayu Ratih (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
The potential market increase leads to an increase in the cosmetics industry. The back to nature trend, the availability of raw materials and the support of the tourism industry, especially in Bali, opens up opportunities for the development of natural-based cosmetics, one of which is Bali Stuti from PT. Karya Pak Oles Tokcer. The purpose of this study is to analyze the product’s attribute (quality; brand; design and packaging) that affect customer satisfaction of Bali Stuti. This research is an analytical study using a questionnaire instrument with a 4-point Likert scale with favorable and unfavorable statements and filled in by respondents that meet the inclusion criteria. Sampling techniques with incidental sampling. The questionnaire was tested for validity and reliability and then analyzed using multiple linear regression. The results of the study found that the product’s attributes affect customer satisfaction. Design and packaging factors partially have a positive and significant impact on customer satisfaction, so there is a need for development and innovation in design and packaging to increase customer satisfaction.